The Influence of Social Media Marketing and Self-Concept on Brand Loyalty by Applying the Flow Experience Theory in Islamic-Based Online Course - Aldy Maulana Ibrahim; Endy Gunanto Marsasi (Jurnal Manajemen Bisnis, 2023)
This research investigates the correlation between social media marketing and self-concept on brand awareness, brand image, and brand loyalty among Generation Y and Z in the Muslim Creator Class, an online course that creates content based on Islamic values. The research employs a quantitative approach with convenience sampling, resulting in 290 samples. Structural Equation Modeling (SEM) analysis was carried out with the assistance of AMOS 26 Graphics software. The main findings reveal that social media marketing significantly correlates with brand awareness, brand image, and brand loyalty. A novel discovery in this research shows that social media marketing is significantly positively related to self-concept. Brand awareness has a significant positive association with brand loyalty, while self-concept does not significantly influence brand image, and brand image has a significant negative impact on brand loyalty. The implications of this research are relevant for companies like Muslim Creator Class to strategically utilize positive and value-aligned social media marketing to target Generation Y and Z, presenting inspirational, educational content that aligns with Islamic values.